Making media : - Roberts-Breslin, Jan (Focal Press, 2003)
Making Media takes the media production process and deconstructs it into its most basic components. Students will learn the basic concepts of media production: frame, sound, light, time, motion, sequencing, etc., and be able to apply them to any medium they choose. They will also become well grounded in the digital work environment and the tools required to produce media in the digital age. A CD-ROM, compatible with both Macs and PCs, will provide interactive exercises for each chapter, allowing students to explore the process of media production. The text is heavily illustrated and complete with sidebar discussions of pertinent issues. Focusing on the building blocks that transcend the boundaries between film, television, multimedia, and the Internet, this highly illustrated and interactive text stresses the commonalities of various types of media and prepares the student to succeed within a wide range of disciplines.